2010
DOI: 10.4028/www.scientific.net/amm.34-35.956
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Energy Absorption Characteristics of PVB Laminated Windshield Subject to Human Head Impact

Abstract: In this paper, energy absorption characteristics of PVB laminated windshield subject to human head impact are studied. SHPB method is carried out to obtain the constitutive relationships of PVB laminated glass in dynamic behavior. With the SHPB results embedded, finite element simulation is used to study the dynamic behavior of PVB laminated windshield. In particular, energy absorption characteristics are investigated. Two parameters for measuring the energy absorption property of windshield are suggested, i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…The Polyvinyl Butyral (PVB) laminated windscreen, which is compressed by two pieces of glass and PVB interlayer, has been chosen as the first and optimum material for the windshield due to its light transmittance and adhesive property. Only through further research on the static performance and failure mechanism, can the possible way be found to obtain sufficient safety and lightweight of laminated automotive windscreens [1]. In accordance with the experiment standard of GB/T 5137.…”
Section: Introductionmentioning
confidence: 80%
“…The Polyvinyl Butyral (PVB) laminated windscreen, which is compressed by two pieces of glass and PVB interlayer, has been chosen as the first and optimum material for the windshield due to its light transmittance and adhesive property. Only through further research on the static performance and failure mechanism, can the possible way be found to obtain sufficient safety and lightweight of laminated automotive windscreens [1]. In accordance with the experiment standard of GB/T 5137.…”
Section: Introductionmentioning
confidence: 80%